Cultural boundaries - Lehtonen, Tommi (Wydawnictwo Instytutu Filozofii i Socjologii PAN, 2019)
This paper seeks to resolve the problem of redefining cultural boundaries. Therefore, the following questions are addressed: 1) To what do cultural boundaries refer, and of what do they basically consist? 2) On what conditions and to what extent is the metaphor of cultural boundaries appropriate? 3) On what conditions can cultural boundaries be broken or crossed? These questions are examined based on a philosophical analysis that draws from Dave Elder-Vass’s The Reality of Social Construction (2012) and Alasdair MacIntyre’s Whose Justice? Which Rationality? (2003). As a major result, it is shown that the metaphor of boundaries is an appropriate tool for cultural studies, insofar as it helps to explain why different norms are followed in different cultures, and how cultural conflicts are related to breaking of norms endorsed and enforced by different social groups. The metaphor of boundaries fits this task, because with the help of it different cultures and social groups can be structured and represented as distinct collective entities, yet with blurred and changing borders, that can side, collide, and overlap with each other.
Keywords: cultural boundary; cultural conflict; cultural encounter; norm circle; intercultural learning; cultural differences; culture; multiculturalism; cultural conflicts; norms; Medieval philosophy; identity (mental objects); cultural events; cultural contacts; interculturalism; Filosofia